Measuring Throughput for Fault Tolerant Based ACO Algorithm under Cloud Computing: A Comparison Study - Singh Kushwah, Virendra; K. Goyal, Sandip; Sharma, Avinash (International Journal of Engineering and Technology, 2018)
Any technical problem can be main cause for any fault. Due to any fault, system would be suffered the work and enhance the system cost in term of money and others. There are many algorithms for fault tolerant in cloud computing and make comparison with fault tolerant based ant colony optimization and which is used to minimize fault during load balancing. In this paper, throughput is measured by such kind of fault tolerant based algorithms and determines that which algorithm is better. It has been compared with ACO. After such comparison, it is clearly determined that ACO has good functionalities to have better throughput. Comparative study is shown by the graphically and finally described that ACO is better than others in context of throughput calculation are. ACO is itself a meta-heuristic algorithm and better optimization technique.Â Â